Dual band four port MIMO antenna with dual circular polarization for Wi-Fi/WiMAX applications - Poonam Thanki; Trushit Upadhyaya; Upesh Patel; Khaled Aliqab; Meshari Alsharari; Ayman A. Althuwayb; Ammar Armghan; Vishal Sorathiya (Alexandria Engineering Journal)
The planar compact four port circularly polarized printed MIMO antenna described in this article is small and intended to support Wi-Fi and WiMAX applications. Suggested four E-shaped monopole elements make up the dual circularly polarized (CP) MIMO antenna that has two left hand CP (LHCP) elements and two right hand CP (RHCP) elements. An I shaped strip is used to join separate ground planes of designed E shaped monopole antenna to have same voltage levels. A good diversity performance is achieved with an envelope correlation coefficient (ECC) of less than 0.15. The 60 mm × 60 mm antenna is designed from FR4 material, which is inexpensive and has a 1.6 mm thickness. Using a high-frequency structure simulator (HFSS), the suggested MIMO antenna is designed and optimized. The measured findings demonstrate the circular polarization, 3-dB axial ratio beamwidth, impedance bandwidth of 2.11 GHz −2.42 GHz and 3.40 GHz-3.51 GHz, adequate axial ratio bandwidth (ARBW) of the suggested MIMO antenna along with high isolation of −17 dB, gain of 3.43 and 2.09 dBic at 2.4 GHz and 3.5 GHz respectively, TARC (Total active reflection coefficient) of less than 0 dB, a CCL (Channel capacity loss) of lesser than 0.4 bits/sec/Hz, and an MEG (Mean effective gain) value of less than 3 dB.